Kontroversi Penerapan Hukum Islam pada LGBT di Brunei Darussalam - Rohmaniah, Dinda Alfiatur; Qodarsasi, Umi; Dewi, Tevana Sari; Utami, Tri (State Islamic Institute of Kudus (IAIN Kudus), 2020)
Controversy of Sharia Law Against LGBT in Brunei Darussalam . This paper aims to discuss the application of sharia law in Brunei Darussalam, especially in sharia law for LGBT people. What about the effect of the stricter application of sharia law if applied in Brunei Darussalam. The aim of implementing Sharia law in Brunei Darussalam. Darussalam is none other than the teachings of Islam in Brunei Darussalam that have become stronger than before as a country that has always been devoted to Allah. Even though in its application, Brunei Darussalam has received harsh criticism from the world for the application of sharia law that is enforced in its country, however, criminal law hard and sharia law continues to be implemented after being postponed and finally implemented on April 3, 2019. This article uses a case study approach and analysis with qualitative methods. russlam continues to be implemented even though it has generated a lot of controversy from outside, especially regarding the stoning of adultery and LGBT perpetrators, especially from the United Nations, enforcement of this law violates human rights. The background to the adoption of sharia law is nothing more than strengthening the quality of the involvement of Muslims in Brunei Darussalam which is only for Allah.